ANALISIS WACANA KRITIS BAHASA DAN STRATEGI MEDIA SOSIAL CAKRA ABHIPRAYA RESPONSIF DALAM HABITUS - Nadira Maurizka Kuputri (Jurnal Ilmu Komunikasi Acta Diurna, 2020)
The pandemic caused by Coronavirus Disease (COVID-19) has an impact on all levels of society in Indonesia. The people who are below the poverty line are no exception. The government's call for physical distancing by stopping many sectors of the economy, further worsening the welfare of the underprivileged. One of non-governmental social organization that was launched on its Instagram page, helping a lot of those in distress, is the Chakra Abhipraya Responsif. In carrying out its activities, the Cakra Abhipraya Responsif is assisted by many parties which makes it easier for them to reach more targets with maximum results. This research tries to look at the communication strategy launched by the Cakra Abhipraya Responsif and their fundraising program through the language they use on their Instagram page. Using Fairclough's critical discourse analysis, the text is analyzed through three components, namely text, discourse practice, and socio-cultural practice. Then by discussing Bourdieu's theory of Habitus and looking far behind the scenes, it can be concluded that social capital in the form of the background/relations of the Cakra Abhipraya Responsif volunteers influences a lot in the implementation of their activities. Although information about social organizations is quite minimal on the internet. The Cakra Abhipraya Responsif communication strategy uses a caption writing style that flicks the audience by focusing their fundraising on communities whose economies have indeed been in decline long before the existence of this pandemic. Keywords: COVID-19, communication strategy, critical discourse analysis, social capital, habitus